1962
DOI: 10.1161/01.res.10.5.817
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Responses of Rats with Spontaneous Hypertension and Control Rats to Pressor Drugs and to Hexamethonium

Abstract: • A difficulty in studying the pathogenesis of essential hypertension is that spontaneous hypertension is not frequent in experimental animals. Most experimenters have used animals in which hypertension has been induced, usually by the production of renal ischemia. As essential hypertension in man is inheritable, an attempt was made to develop a spontaneous hypertension by selective breeding from rats with overaverage blood pressures. Eventually a strain of Wistar rats with overaverage blood pressures was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1965
1965
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The response to NA in vivo was unaffected by L ‐NAME and similar in GH and N rats, the latter finding similar to previous studies. 33,34 Changes in HR in response to NA were similar in the different experimental groups, indicating that baroreflex activity is similar and, therefore, could not have masked differences in constrictor response. In the hindquarter, the response to NA was larger in GH rats, which is consistent with other findings in this and the mesenteric vascular bed.…”
Section: Discussionmentioning
confidence: 85%
“…The response to NA in vivo was unaffected by L ‐NAME and similar in GH and N rats, the latter finding similar to previous studies. 33,34 Changes in HR in response to NA were similar in the different experimental groups, indicating that baroreflex activity is similar and, therefore, could not have masked differences in constrictor response. In the hindquarter, the response to NA was larger in GH rats, which is consistent with other findings in this and the mesenteric vascular bed.…”
Section: Discussionmentioning
confidence: 85%
“…Increased vascular reactivity has also been shown in the intact adult GHR (Phelan et al 1962) and in the pithed GHR rat preparation (Jones et al 1976). Phelan et al (1 979) showed specifically that vascular reactivity to adrenaline and noradrenaline was enhanced in young GHR.…”
Section: Discussionmentioning
confidence: 93%
“…We decided to use a low-dose Ang II infusion protocol because rats infused with a high-dose Ang II show strong hypertensive response 13,14 , and it has been shown that animals with high blood pressure fail to respond to pressor compounds 15,16 . We found that infusion of Ang II alone significantly increased BP for the first 5 days of infusion, while the concomitant infusion of Ang II and TMAO produced sustained increase in BP, which suggests that TMAO prolonged the hypertensive effect of Ang II.…”
Section: Effects Of Chronic Infusion Of Tmao and Ang II On Motor Actimentioning
confidence: 99%